Reflections On Employment Protection Legislation: An International Comparison - Amine, Samir (Comparative Economic Research. Central and Eastern Europe, 2015)
In Europe, as in the rest of industrialized countries, reforms of the labour market have generally concerned employment protection legislation (EPL). One of the main missions of this legislation is to insure security for workers, particularly in case of redundancy. The object of this article is to compare the strictness and the degree of rigidity of EPL in two different economies, namely, Canada and France. This choice is justified by the fact that the labour market policies in both countries do not have the same orientation and are based on different ideological references.